Hormesis and Paradoxical Effects of Drooping Birch ( Roth) Parameters Under Motor Traffic Pollution - Elena A. Erofeeva (SAGE Publishing, 2015)
Various plant indexes are used or recommended for bioindication. However, the nonmonotonic dose-response dependences (hormesis and paradoxical effects) of these indexes are insufficiently explored upon exposure to pollution. We studied the dependences of these Betula pendula indexes on the intensity of motor traffic pollution. Regression analysis did not reveal any dependence of chlorophyll and carotenoid content on traffic intensity (in 2008 and 2010-2013). Lipid peroxidation rate had different versions of paradoxical effects in 2008 and 2010 to 2012 and increased in comparison with control under an increase in pollution level in 2013. In 2010 to 2012, all dose-response dependences for total protein and thiol group content were biphasic and multiphasic paradoxical effects. In 2013, an increase in traffic intensity induced a linear reduction in protein content and an increase in thiol group level in comparison with the control. In most cases, the studied phenological indexes and seed production decreased monotonically in comparison with the control following an increase in traffic intensity. Only in 2010 and 2013, share of fallen leaves had hormesis and paradoxical effect accordingly. Fluctuating asymmetry had a paradoxical effect and hormesis in 2008 and 2012, accordingly, and increased in comparison with the control under an increase in the level of pollution in 2010 to 2011.